Study of Cultural Preservation and Protection of Cultural Values through Ethnocentricity of Domestic Products - Suryowati, Budi (INOVATOR, 2023)
Globalisasi influence human behavior in the sphere of life. Changes in people's behavior include lifestyle, one of which is the desire to use foreign products. This study wanted to determine how ethnocentric consumers were among Trilogi University students, who numbered 2,289. To assess consumer ethnocentrism use CETSCALE as a measure. With the Structural Equation Modeling (SEM) method, the results showed that their opinions on ethnocentricism in the form of protectionism, socio-economic conservatism, and ultra-nationalism affected the unwillingness to buy foreign products, and opinions about nationalism did not affect the unwillingness to buy foreign products.